2021
DOI: 10.2519/jospt.2021.10598
|View full text |Cite
|
Sign up to set email alerts
|

The Altmetric Score Has a Stronger Relationship With Article Citations Than Journal Impact Factor and Open Access Status: A Cross-sectional Analysis of 4022 Sport Sciences Articles

Abstract: Objective To assess the relationship of individual article citations in the sport sciences field with (1) Journal Impact Factor, (2) each article's open access status, and (3) Altmetric score components. Design Cross-sectional. Methods We searched the Web of Science Journal Citation Reports database in the sport sciences category for the 20 journals with the highest 2-year Journal Impact Factor in 2018. We extracted the impact factor for each journal and each article's open access status (yes or no). Between S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 30 publications
0
8
1
Order By: Relevance
“…Prior literature on the impact of open access status has been conflicting. For example, Silva et al identified a weakly positive association among sports medicine articles [ 5 ], but an inverse relationship has also been identified in other fields [ 19 ]. Overall, a weak effect of open access status and citations may be due to the prevalence of institutional availability of non-open-source articles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior literature on the impact of open access status has been conflicting. For example, Silva et al identified a weakly positive association among sports medicine articles [ 5 ], but an inverse relationship has also been identified in other fields [ 19 ]. Overall, a weak effect of open access status and citations may be due to the prevalence of institutional availability of non-open-source articles.…”
Section: Discussionmentioning
confidence: 99%
“…Within the field of orthopaedic surgery, the "#OrthoTwitter" community on the Twitter platform has evolved as a forum to disseminate findings, exchange ideas, and connect with both the public and other practitioners [2][3][4]. It has been suggested that Twitter activity at the time of publication is associated with academic citation counts after several years [1,5,6]. However, the academic impact of social media utilization, particularly by authors, remains uncertain in the orthopaedic surgery community.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We will disseminate the findings in peer-reviewed journals and social media 101. We expect to publish several articles based on data collected at the baseline and follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…Scarlat et al 23 mentioned that high-volume publications also have a high-volume social media impact. Silva et al 24 reported that the AAS exerted a stronger relationship with the number of citations than the journal impact factor and open access status in sports sciences journals. Hughes et al 15 demonstrated that journals with higher numbers of retweets had higher AAS and were positively associated with impact factor.…”
mentioning
confidence: 99%